Variability in pulmonary function test reporting: A survey of respirologists in Canada. Issue 6 (8th December 2022) - Sparrow, Kaitlin; Wong, Eric; Cheung, Lawrence; Wang, Melissa; Vethanayagam, Dilini; Li, Pen
Abstract: Rationale: The interpretation of pulmonary function tests (PFTs) is not standardized. Many guidelines exist, both disease specific and physiologically based, which lead to variability in PFT interpretations and may impact patient care. Objectives: We examine how respirologists in Canada interpret PFTs, what content they report and how this compares to current societal guidelines. Methods: An anonymous survey was sent to Canadian respirology training programs and forwarded to respirologists affiliated with their city. Comparisons were made using chi-square testing and variability measured using the index of qualitative variation (IQV). Results: There were 103 respondents; 78 (76%) were staff respirologists, representative of about 10% of practicing adult respirologists. The IQV ranged from 0.64 to 0.95 for defining obstruction and severity, bronchodilator response, lung volumes, and diffusion abnormalities and severity. No significant differences were detected between staff physicians and trainees or those in tertiary versus community practice, when defining obstruction, lung volumes and diffusion abnormalities. Pediatric respirologists were more likely ( p < 0.001) to use Canadian Thoracic Society (CTS) asthma guidelines to define an obstructive defect. One specific diagnosis ( p = 0.036) and a differential diagnosis ( p = 0.027) were more likely to be included in a PFT summary if the ordering physician was a family physician compared to a respirologist or non-respirology specialist compared to a respirologist, respectively. Conclusions: There is large variability in how PFTs are interpreted and summarized by respirologists in Canada. Our study highlights the need for quality assurance and development of a national consensus of reporting PFTs.